Pemanfaatan Produksi Pakan Mandiri untuk Meningkatkan Efisiensi Usaha Budidaya Ikan - Nurjamiyah Nurjamiyah; Haida Dafitri; Zaharuddin Zaharuddin; Kalvin Chiuluto; Sumi Khairani; Lisa Adriana (JPM: Jurnal Pengabdian Masyarakat, 2026)
Feed costs are the largest component in fish farming businesses, accounting for more than 60% of total production costs. This condition is also experienced by fish farmer groups in Patumbak Village, Deli Serdang Regency, which still depend on commercial feed, resulting in high operational costs and reduced profits. On the other hand, the area has local resources that can be utilized as alternative feed ingredients, one of which is chicken feather waste, which contains a high protein content. However, the limited knowledge and skills of the partners in producing self-made feed have become the main obstacle to utilizing this potential. This community service program aimed to improve the knowledge and skills of fish farmer groups in producing self-made feed based on chicken feather waste to enhance the efficiency of fish farming businesses. The partner of this activity was a fish farmer group managed by Mr. Denianto in Patumbak Village, Deli Serdang Regency. The implementation methods included socialization, self-made feed production training, feed production practice, mentoring, and evaluation. The results showed an improvement in participants’ knowledge and skills regarding feed formulation and self-made feed production. The partners were able to utilize chicken feather waste as an alternative feed ingredient, thereby reducing their dependence on commercial feed. Furthermore, the program had a positive impact on production cost efficiency, strengthened group collaboration, and encouraged more environmentally friendly utilization of livestock waste. This program is expected to support the sustainability of fish farming businesses and improve the welfare of fish farming communities in Deli Serdang Regency.